Idiopathic Eruptive Macular Pigmentation with Papillomatosis: A Common but Underdiagnosed Entity - Vineet Relhan; Ishan Agrawal; Rekha Yadav (Wolters Kluwer Medknow Publications, 2024)
Idiopathic Eruptive Macular Pigmentation (IEMP) is an uncommon and possibly underdiagnosed dermatosis. It manifests as asymptomatic pigmented macules over the face, trunk and proximal extremities among children and adolescents. Degos et al. first documented this condition in 1978, unveiling its distinct characteristics. The macules, initially dark brown-black, naturally diminish over several months to years, with no lasting pigmentation or scarring. In this report, we highlight the case of a 14-year-old girl displaying all the distinctive traits of IEMP.